High-resolution body wave tomography beneath the SVEKALAPKO array — II. Anomalous upper mantle structure beneath the central Baltic Shield - Sandoval, Senén; Kissling, Edi; Ansorge, Joerg (2017)
A number of different geodynamic models have been proposed to explain the early tectonic evolution of the Baltic Shield. To provide additional geophysical constraints on these models, we performed a teleseismic tomography traveltime inversion for the central part of the Baltic Shield. The SVEKALAPKO project is focused on the investigation of the lithosphere—asthenosphere structure down to 400 km depth under central Fennoscandia (Baltic Shield). A total of 143 stations were deployed including 15 permanent stations from the Finnish seismic network. The temporal network was composed of 40 broad-band and 88 short-period instruments distributed in a rectangular array of 1000 km by 900 km from 1998 August to 1999 May. The results are based on a non-linear teleseismic tomography algorithm. They reveal significant P-velocity variations (up to 4 per cent) throughout the SVEKALAPKO array. The most prominent feature is a positive anomaly that can be followed down to 250 km depth beneath the centre of the array. We interpret this anomaly as the signature of the tectosphere (Jordan 1978) beneath the Fennoscandian Shield. It correlates spatially with an anomalous high-velocity lower crust. Other shallow (crustal) anomalies can be correlated with magmatic events surrounding this nucleus of high velocity. Comparison of images before and after correction by crustal structure proves that this methodology yields solid and coherent tomographic results. Further observations of relative P traveltime residuals from six teleseismic events with different azimuths show delay variations of ±2.0 s between stations located in the North German basin and stations on the Svecofennian Shield